2013
DOI: 10.1523/jneurosci.4338-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Cortical and Thalamic Input to Pyramidal Neurons in Mouse Motor Cortex

Abstract: Determining how long-range synaptic inputs engage pyramidal neurons in primary motor cortex (M1) is important for understanding circuit mechanisms involved in regulating movement. We used channelrhodopsin-2 (ChR2)-assisted circuit mapping to characterize the long-range excitatory synaptic connections made by multiple cortical and thalamic areas onto pyramidal neurons in mouse vibrissal motor cortex (vM1). Each projection innervated vM1 pyramidal neurons with a unique laminar profile. Collectively, the profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
418
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(453 citation statements)
references
References 58 publications
(109 reference statements)
32
418
3
Order By: Relevance
“…cortex (55), which could be a single source of both drives. In motor cortex, two distinct thalamocortical projection pathways to primary motor cortex in proximal and distal projection patterns have been shown to emerge from distinct thalamic zones (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…cortex (55), which could be a single source of both drives. In motor cortex, two distinct thalamocortical projection pathways to primary motor cortex in proximal and distal projection patterns have been shown to emerge from distinct thalamic zones (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…One emerging principle from these experiments is lamina-specific connectivity, which has great functional implications. On the input side, for example, it has been found that basal ganglia–recipient and cerebellum-recipient nuclei of the thalamus project asymmetrically to the motor cortex, with the former projecting predominantly to layer 1 apical dendrites of layer 2/3 and layer 5 neurons, whereas the latter projects directly to layer 2/3 and, to a lesser extent, to layer 5 (Hooks et al 2013; Kuramoto et al 2009, 2013). The differential projection patterns of these two thalamic recipient zones suggest that information from the basal ganglia and cerebellum may take different routes through the motor cortex and partake in different types of computation.…”
Section: Comparative Anatomical and Functional Features Of The Motomentioning
confidence: 99%
“…Inputs from other cortical areas also arrive with characteristic laminar profiles. For example, somatosensory areas primarily drive layers 2/3 and 5a (Mao et al 2011), whereas frontal areas are biased toward contacting layers 5 and 6 (Hira et al 2013b, Hooks et al 2013, Rouiller et al 1993). Within the motor cortex, the predominant flow of information travels from superficial to deep layers (Weiler et al 2008).…”
Section: Comparative Anatomical and Functional Features Of The Motomentioning
confidence: 99%
See 2 more Smart Citations